Quercetin Modulates IGF-I and IGF-II Levels After Eccentric Exercise-Induced Muscle-Damage: A Placebo-Controlled Study - Sgrò, Paolo; Ceci, Roberta; Lista, Marco; Patrizio, Federica; Sabatini, Stefania; Felici, Francesco; Sacchetti, Massimo; Bazzucchi, Ilenia; Duranti, Guglielmo; Di Luigi, Luigi (Frontiers in Endocrinology, 2021)
Background: Prolonged or unaccustomed eccentric exercise may cause muscle damage and depending from its extent, this event negatively affects physical performance. Objectives: The aim of the present investigation was to evaluate, in humans, the effect of the antioxidant and anti-inflammatory flavonoid quercetin on circulating levels of the anabolic insulin-like growth factor 1 (IGF-I) and insulin-like growth factor 2 (IGF-II), produced during the recovery period after an eccentric-induced muscle damage (EIMD). Methods: A randomized, double-blind, crossover study has been performed; twelve young men ingested quercetin (1 g/day) or placebo for 14 days and then underwent an eccentric-induced muscle damaging protocol. Blood samples were collected, and cell damage markers [creatine kinase (CK), lactate dehydrogenase (LDH) and myoglobin (Mb)], inflammatory status [interleukin 6 (IL-6)] and IGF-I and IGF-II levels were evaluated before the exercise and at different recovery times from 24 hours to 7 days after EIMD. Results: We found that, in placebo treatment the increase in IGF-I (72 h) preceded IGF-II increase (7 d). After Q supplementation there was a more marked increase in IGF-I levels and notably, the IGF-II peak was found earlier, compared to placebo, at the same time of IGF-I (72 h). Quercetin significantly reduced plasma markers of cell damage [CK (p<0.005), LDH (p<0.001) and Mb (p<0.05)] and the inflammatory interleukin 6 level [IL-6 (p<0.05)] during recovery period following EIMD compared to placebo. Conclusions: Our data are encouraging about the use of quercetin as dietary supplementation strategy to adopt in order to mitigate and promote a faster recovery after eccentric exercise as suggested by the increase in plasma levels of the anabolic factors IGF-I and IGF-II.